Formulation of Objective and Key Result and Key Performance Indicator Framework as a Performance Measurement System in Yayasan Perdamaian Indonesia - Kinanti, Khisi; Hartanti, Dwi (INOVASI, 2025)
Nonprofit organizations increasingly face pressure from donors to demonstrate accountability, transparency, and measurable impact beyond program outputs. Yayasan Perdamaian Indonesia (YPI) has experienced a sustained decline in external funding over the past six years despite expanding program activities, indicating the absence of an effective performance measurement system to support fundraising credibility. This study aims to formulate an integrated Objectives and Key Results (OKR) and Key Performance Indicators (KPI) framework as a performance measurement system to strengthen YPI’s external fundraising capacity. A qualitative single-case study approach was employed, with YPI as the unit of analysis. Data were collected through semi-structured interviews, a focus group discussion, non-participant observations, internal document analysis, and benchmarking with nonprofit organizations in Malaysia and the Philippines. The data were analyzed using thematic narrative analysis. The findings reveal critical organizational challenges, including weak program documentation, fragmented impact reporting, limited strategic communication, and underdeveloped partnership management. Based on these findings, four strategic OKR objectives were formulated and translated into a set of operational KPIs covering documentation, fundraising, communication, and partnerships. The proposed OKR KPI framework provides a structured and measurable mechanism to align strategic objectives with operational performance, enhance organizational accountability, and improve YPI’s ability to attract sustainable external funding.